An improved ant algorithm for Multi-mode Resource Constrained Project Scheduling Problem∗. Issue 4 (11th July 2014) - Wuliang, Peng; Min, Huang; Yongping, Hao
Abstract : Many real-world scheduling problems can be modeled as Multi-mode Resource Constrained Project Scheduling Problems (MRCPSP). However, the MRCPSP is a strong NP-hard problem and very difficult to be solved. The purpose of this research is to investigate a more efficient alternative based on ant algorithm to solve MRCPSP. To enhance the generality along with efficiency of the algorithm, the rule pool is designed to manage numerous priority rules for MRCPSP. Each ant is provided with an independent thread and endowed with the learning ability to dynamically select the excellent priority rules. In addition, all the ants in the ant algorithm have the prejudgment ability to avoid infeasible routes based on the branch and bound method. The algorithm is tested on the well-known benchmark instances in PSPLIB. The computational results validate the effectiveness of the proposed algorithm.